Does the pilot construction of new-energy cities promote particulate matter 2.5 (PM2.5) reduction? Evidence from China - Yang, Mingwei; Yang, Wenju; Wang, Zheng; Liu, Jun (Frontiers in Environmental Science, 2023)
Introduction: In recent years, China has paid high attention on urban energy innovation, trying to achieve a win–win situation between environmental protection and urban development, and it has formulated a series of policies to promote urban energy innovation. Methods: Taking China’s new energy demonstration city (NEDC) policy as an example, this paper empirically investigates the impact of China’s urban energy policy on PM2.5 by using a difference-in-differences (DID) model. Results/Discussion: (1) NEDC policy has reduced PM2.5 concentrations by 4.84% in pilot cities. Moreover, this policy can continue to reduce PM2.5 concentrations for at least 5 years, and the policy effect increases year by year. (2) NEDC policy has spatial spillover effect, which significantly reduces PM2.5 of surrounding cities within 150 km. (3) The PM2.5 reducing effect of NEDC policy is primarily the result of technological effect and allocation effect generated by promoting innovation and industrial upgrading. (4) The PM2.5 control effect of NEDC policy presents an inverted U-shape with the expansion of city size, and is better in cities with low levels of financial support, high levels of human capital and information infrastructure. The conclusions of this paper have important theoretical value for understanding the ecological effect of innovation policy and provide experience for developing countries to implement an experimentalist governance model.